Verbless Relative Clauses in Gǝʿǝz and their Equivalents in Amharic and Tigrinya - Kapeliuk, Olga (Aethiopica, 2009)
The most frequent and most typical relative clauses in Gǝʿǝz have a verbal predicate, but also nominal, or in other terms verbless, sentences may be relativized. Since Gǝʿǝz has no copula, nominal sentences are composed of the subject and of the predicative complement of a zero copula only. Considering that in sentences with relative clauses the headnoun stands outside the relative clause, all that is left in the latter is the relative pronoun and what acts as the predicative complement. Hence the nominal relative clauses have a much reduced structure and may be interpreted wrongly as one-member sentences.